L'industrie du silex du ve au ive millénaire dans le sud-est du Bassin parisien Rubané, Villeneuve-Saint-Germain, Cerny et groupe de Noyen - Augereau, Anne (Documents d'archéologie française, 2004)
The Seine-Yonne sector occupies a special place in our knowledge of Neolithic societies. Although an interface between the southern and north-eastern branches, it is also the exclusive preserve of chalk flint. Applying the "technological system" concept, the author seeks to identify the skills levels of the flint knappers, asks whether expert knappers existed, and explores the spatial breakdown of the operational chain and the methods of acquiring and distributing raw materials in order to address the question of the socio-economic organization of flint tool production. Her exploration is based on the study of twelve reference series comprising over 100.000 flint artifacts in a multivariate analysis making use, among other approaches, of cladistics, the first time this technique has ever been applied to this field. By systematically referring to anthropological and historical questions, this book constitutes an important contribution to the study of the development of Neolithic communities across Europe.